Watercolor 365 daily tips, tricks and techniques - Redhead, Leslie (North Light Books, 2017)
A year's worth of tips, techniques, advice and more! Make watercolor a part of your daily life, turning every day into inspiration for your art. Designed to fit your life, Watercolor 365--the first watercolor book of its kind--provides a complete education in the medium, one bite-sized bit of information at a time. Open it daily to find a new tip, idea, technique or challenge...all aimed at getting you into the habit and mindset of an artist.